Immune checkpoint inhibitor-induced isolated adrenocorticotropic hormone deficiency: a systematic review - Wang, Fen; Shi, Xiaoli; Yu, Xuefeng; Yang, Yan (Frontiers in Endocrinology, 2024)
Background: Immune checkpoint inhibitor induced isolated adrenocorticotropic hormone deficiency (IAD) is a rare but potentially fatal disease.We comprehensively searched PubMed database and made a systematic review of immune checkpoint inhibitor induced isolated adrenocorticotropic hormone deficiency. If no other anterior pituitary hormones were mentioned in the case, they were excluded.We identified 123 cases diagnosed as immune checkpoint inhibitor induced IAD, including 44 female and 79 male. The average age of these patients was 64.3 ± 12.6 years old, and 67.5% were 60 years old or above. The majority (78.9%) of these patients received anti-programmed cell death protein-1 (anti-PD-1) antibodies or antiprogrammed cell death ligand 1 (anti-PD-L1) antibodies or both, 19.5% received combined therapy, sequential therapy or both. A total of 26 patients received anticytotoxic T lymphocyte antigen 4 antibodies (anti-CTLA-4). The median ICIs treatment cycles before the diagnosis of adrenal insufficiency was 8 (6, 12) and the median ICIs treatment duration before the diagnosis of adrenal insufficiency was 6 (4, 8) months. Eleven cases of IAD occurred 1 to 11 months after ICIs was stopped. Fatigue and appetite loss were the most common symptoms, and surprisingly, there were 2 asymptomatic cases of IAD. Most patients (88 cases) had a normal pituitary magnetic resonance imaging, while only 14 cases reported mild atrophy or swelling pituitary gland and 21 cases reported no imaging results. Most diagnoses were made by basal hormone levels, and pituitary stimulation tests were performed in only a part of cases.No cases had been reported of discontinuation of ICIs use due to IAD, nor had there been any deaths due to IAD.IAD was predominant in elderly male patients who mainly receiving anti-PD-1 or anti-PD-L1 antibodies. It was sometimes difficult to recognize IAD at the first glance since nonspecific symptoms were common and asymptomatic cases of IAD were also reported. Although IAD can be deadly, it usually does not affect whether to continue using ICIs.